Relationship between Industrial Production, Financial Development and Carbon Emissions: The Case of Turkey - Gokmenoglu, Korhan; Ozatac, Nesrin; Eren, Bans Memduh (Elsevier Science Bv, 2015)
It is widely accepted that industrialization causes air pollution due to increased fossil fuel consumption. On the other hand, recent literature related with the impacts of financial development on air pollution has produced some mixed results. It is argued that not having proper energy policies has become a more severe problem for Turkey as the industrial activities have been accelerated in the country. The present study investigates the long run relationship between industrialization, financial development and carbon emissions by using Granger causality test in Turkey. Findings of the present study reveal a unidirectional relationship from financial development to carbon emissions. (C) 2015 The Authors. Published by Elsevier B.V.
16th Annual Conference on Finance and Accounting (ACFA) -- MAY 29, 2015 -- Prague, CZECH REPUBLIC
Keywords: Industrialization; Financial development; Air pollution; Granger Causality